Comparative test of flavonoids and saponins between leaves and flowers of knobs (Gomphrena globosa l.) as anti-nausea and antioxidant therapy in cancer patients undergoing chemotherapy - Anisa Balqis Shoim; Alfisya Salsabillah; Fatiyah Putri Anjani; Shofi Zakiyatul Fuadah Ar Ramadhani (Universitas Airlangga, 2021)
Cancer is one of the leading causes of death in the world today. In 2018, there were 18.1 million new cases of cancer with a death rate of 9.6 million. Chemotherapy is one way of cancer treating. Effects of chemotherapy include gastrointestinal symptoms such as nausea, vomiting, stomatitis and myelo suppression in the form of anemia, leukopenia, and thrombocytopenia. Symptoms of nausea and vomiting are one of the most serious side effects. This condition can cause patient choose to stop therapy. Discontinuation of therapy has the potential to increase cancer progression. If not treated quickly, it will cause malnutrition. The knob plant (Gomhprena globosa l.) is a nutritious plant that has been used in traditional medicine. Knobs have potential as antioxidants of it flavonoids. The flavonoid and saponin compounds can accelerate the digestive system and act as an anti-nausea, making it suitable as therapy for patients with chemotherapy. This study aims to compare the flavonoid and saponin between the leaves and knob flowers which are best used as anti-nausea products. The research was conducted at the Chemical Laboratory of MAN 1 Gresik. The extraction method used in this is maceration. The steps for testing flavonoids and saponins on knob leaves and flowers can be done by pounding the leaves and knob flowers, labeling 4 test tubes, namely, F flowers for the Flavonoid test, S flowers for the Saponins test, F leaves for the Flavonoid test, S leaves for the Saponins test. Then, add 1 ml of leaf and flower extracts into test tube, add magnesium tape to the test tube labeled F leaves and F flowers, add 1 ml of concentrated HCl into the test tube labeled F, then enter 1 ml of HCl 2N on the test tube labeled S leaves and S flowers. Based on this study, can be concluded that knob leaves have higher flavonoids and saponins. Fact, knob leaves produce more yellow color. In the saponin test, the leaf had more foam than the flower. Therefore, knob leaves can be used as anti-nausea and antioxidants in cancer patients with chemotherapy.